Mapping Agroforestry and Trees Outside Forest - Rizvi, R.H.; Handa, A.K.; Sridhar, K.B.; Kumar, A.; Bhaskar, S.; Chaudhari, S.K.; Arunachalam, A.; Thomas, N.; Ashutosh, S.; Sapra, R.K.; Pujar, G.; Singh, R.K.; et al. (ICAR, Central Agroforestry Research Institute (CAFRI), Jhansi and World Agroforestry (ICRAF), South Asia Regional Programme, 2020)
Mapping the Extents of Agroforestry using Geo-informatics Agroforestry is a collective name for land-use systems and practices in which woody perennials are deliberately integrated with crops and/or animals on the same land-management unit. The integration can be either in a spatial mixture or in a temporal sequence. There are normally both ecological and economic interactions between the woody and non-woody components in agroforestry. In recent years, there has been a shift in the focus of agroforestry research from the plot or field scale to the landscape scale, which has uncovered the multiple benefits that trees provide in agricultural landscapes. But the spatial distribution and extent of agroforestry was not well understood earlier due to the complexity involved in accurately mapping agroforestry and Trees Outside Forest (TOF) in mixed tree/crop/ livestock systems. As per ISFR 2019, all trees growing outside recorded forest areas irrespective of patch size are referred as Trees Outside Forest. A major problem in estimating the area under agroforestry is the lack of procedures for delineating the area influenced by trees in a mixed stand of trees and crops. Besides, simultaneous agroforestry where the tree and the crop components grow at the same time and in close enough proximity for interactions to occur is more complex. As in simultaneous systems, the entire area occupied by multistrata systems such as home gardens, shaded perennial systems and intensive treeintercropping situations can be listed as agroforestry. The problem is more difficult in the case of practices such as windbreaks and boundary planting where trees are planted at a wide distance between rows (windbreak) or around agricultural fields (boundary planting). In such cases, the influence of trees extends over a larger area than is easily perceivable. In addition, there is a general lack of systematically collected ground reference information for the development of predictive models for the extent of agroforestry area, as well as for the validation of these estimates.